Lessons from Armenia's Institutional and Governance Review - Mukherjee, Amitabha; Shahzadeyan, David (World Bank, Washington, DC, 2012)
Institutional and Governance Reviews (IGRs) are a new tool in the Bank's package of analytical and advisory activities (see PREMnote 75). Because they are politically sensitive, the development of these reviews involves careful tradeoffs. Though each requires thorough analysis of a country's institutional shortcomings, the final product must be acceptable to country authorities and other development partners. To be credible and acceptable, an IGR must reflect extensive participation by a variety of national stakeholders. In Armenia the Bank's IGR team engaged the government (executive, legislature, judiciary), civil society (nongovernmental organizations, political parties, trade unions, academics), and other development partners from the outset. This approach resulted in widespread acceptance of the report's analysis and recommendations within both Armenia and the Bank. Armenia's IGR was a pioneering effort by the Bank's Europe and Central Asia Region to systematically evaluate a country's public institutions and develop a program of reforms supported by follow-up operations. The IGR had two main objectives. First, it was to diagnose institutional dysfunction at the national level using quantitative benchmarks of performance. Second, it was to assess political realities and constraints to reform, to foster the sustainability of Bank operations. Armenia was chosen for several reasons. There was a dearth of analytical work on public sector institutional reforms prior to 1998. Moreover, country authorities evinced keen interest in an IGR-and were matched by strong support from the Bank's country unit and team..